A review of the research and advances in electromagnetic joining of fiber‐reinforced thermoplastic composites. Issue 10 (14th August 2019) - Choudhury, Mridusmita Roy; Debnath, Kishore
Abstract : The demand for polymer composites in structural and nonstructural applications has expanded rapidly due to their lightweight, high strength, and stiffness characteristics. Joining of polymer composite is not an easy task as inadequate joint strength leads to failure of a structure due to stress concentration. The following are the three basic methods available for joining of thermoplastic composites: adhesive joining, mechanical fastening, and fusion bonding. Electromagnetic joining is a class of fusion bonding where electromagnetic force is used for generation of heat. Electromagnetic joining has gained new interest among the research fraternity with the development of thermoplastic composites. This type of joining or welding technique offers many advantages over other joining techniques. This joining technique can be used for assembly as well as repairing of thermoplastic polymer‐based composites parts. The main aim of this article is to review the different electromagnetic joining methods for thermoplastic composites and present the recent developments in this area. The electromagnetic joining methods such as induction welding, microwave welding, and resistance welding have been comprehensively discussed in the context of their applicability for joining of thermoplastic polymer‐based composites. POLYM. ENG. SCI., 59:1965–1985, 2019. © 2019 Society of Plastics Engineers